ChemInform Abstract: Scalable and Divergent Total Synthesis of (+)‐Colletoic Acid, a Selective 11β‐Hydroxysteroid Dehydrogenase Type 1 Inhibitor. Issue 12 (25th March 2014) - Ling, Taotao; Griffith, Elizabeth; Mitachi, Katsuhiko; Rivas, Fatima
Abstract An efficient and divergent total synthesis of (+)‐colletoic acid (I), a selective 11‐β hydroxysteroid dehydrogenase 1 inhibitor, is presented along with its biological activity at the whole‐cell level.